2006
DOI: 10.1227/01.neu.0000219218.43128.fc
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diffusion Weighted Mriin Predicting Early Post-Operative Outcome of a New Neurological Deficit Afterbrain Tumor Resection

Abstract: Postoperative diffusion magnetic resonance imaging is useful in predicting early functional recovery from new deficits after brain tumor surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…7 As shown in previous studies, ischemic events after glioma resection are common, occur in 31% of resections for newly diagnosed gliomas, and are more frequent (80%) in patients undergoing resection for recurrent gliomas. 6,7,9,21,23,27 These ischemic lesions correlate with a high incidence of neurological deficits. 6,7 Although it is obvious that direct nonvascular damage to motor-eloquent cortical or subcortical brain areas influences intraoperative MEP monitoring, it is still unclear whether intraoperative vascular damage leading to ischemia can cause intraoperative MEP decline or remains undetectable because of delayed tissue damage.…”
mentioning
confidence: 99%
“…7 As shown in previous studies, ischemic events after glioma resection are common, occur in 31% of resections for newly diagnosed gliomas, and are more frequent (80%) in patients undergoing resection for recurrent gliomas. 6,7,9,21,23,27 These ischemic lesions correlate with a high incidence of neurological deficits. 6,7 Although it is obvious that direct nonvascular damage to motor-eloquent cortical or subcortical brain areas influences intraoperative MEP monitoring, it is still unclear whether intraoperative vascular damage leading to ischemia can cause intraoperative MEP decline or remains undetectable because of delayed tissue damage.…”
mentioning
confidence: 99%
“…The FIM is a rehabilitation measure and does not specifically measure gait, balance, or the specifics of ambulation [23,39,40]. The KPS measures activities of daily living [2]; gait and balance are not considered in scoring. As such, these measures were not appropriate for assessing patient mobility in terms of gait and balance.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have assessed the effectiveness of surgery in minimizing tumor volume, reducing recurrence rates, or increasing survival time following diagnosis [2][3][4][5][6][7]. However, very few studies specifically measure functional outcomes using reliable and valid instruments despite clinical tools to quantify this domain [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of DWI changes following brain tumor resections has been well described [24][25][26] . Khan et al [24] in their prospective study of 80 patients showed that 31 (39%) had a thin marginal pericavity bright DWI signal, considered to be a normal postoperative change.…”
Section: Discussionmentioning
confidence: 99%